PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMEDIASI STRES KERJA, MOTIVASI KERJA DAN TURNOVER INTENTION TERHADAP KINERJA PEGAWAI PADA PT INDAH KIAT PULP & PAPER Tbk - Jubery Marwan (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The main purpose of this research are to test and analyze the role of transformational leadership in mediating work stress, work motivation and turnover intention on employee performance in PT Indah Kiat Pulp Paper Tbk. This research is an explanatory with quantitative approach. This research is done in Pt Indah Kiat Pulp Paper Tbk. Serang regency with using survey method, primary data source that has been tested for its reliability, validity and normality. The population in this research is all of the employee on PT Indah Kiat Pulp Paper Tbk. Serang Regency. Purpossive sampling is used as this research sample selection, Analysis tool that is used is Path Analysis, and specifically used to test hypothesis according to the paradigm of the developed equation model. The research shows that: (1) Work stress variable has a significant effect on Transformational Leadership; (2) Work Motivation Variable has a significant effect on Transformational Leadership; (3) Turnover intention variable has a significant effect on Transformational Leadership; (4) Transformational Leadership Variable Variabel has a significant effect on employee performance; (5) There is positive effect on the Transformational leadership on mediating the effect of work stress and Turnover Intention on employee performance; (6) There is no efeect on Transformational Leadership on mediating the effect of work motivation on employee performance.